Suppressing maize stalk rot through promoted rhizosphere microbial recruitment in cultivar mixtures - An, Panpan; Jia, Xucun; Zhang, Moubiao; Liu, Kui; Wang, Xiuling; Li, Hongping; Zhao, Yali; Wang, Qun; Xie, Mimi; Liu, Tianxue; Li, Chaohai (Frontiers in Microbiology, 2025)
IntroductionCrop diversification is a critical strategy for improving resource use efficiency and suppressing disease. Mixing cultivars from the same crop is one approach to diversifying planting patterns. However, it remains unknown how mixing cultivars in maize affects the soil microbial community, stalk rot incidence, and grain yield.MethodsA 2-year field experiment was performed, which included one stalk rot-resistance cultivar, DH662; one stalk rot-susceptible cultivar, DH701; and a mixture of DH662 and DH701.ResultsCultivar mixtures and DH662 monocrop had lower disease incidence and higher grain yield than DH701 monocrop. The microbial community structure in both rhizosphere and bulk soil was notably impacted by the resistant cultivar as well as the cultivar mixtures. Distinct modules within the rhizosphere microbial community co-occurrence network were identified, differentiating cultivar mixtures from DH701 monocrops. The network structure of the rhizosphere in cultivar mixtures closely resembled that observed in DH662 monocrops. Keystone taxa were higher in cultivar mixtures compared to their abundance in DH701 monocrops. The keystone taxa (Adhaeribacter and Gemmatimonas) were positively related to grain yield and negatively correlated with disease incidence.DiscussionOverall, our results demonstrated that cultivar mixtures had a substantial impact on the assembly and keystone taxa of microbial communities in the rhizosphere and bulk soil, leading to a reduction in stalk rot occurrence and an increase in grain yield. This study demonstrated the potential for maize yield improvement through cultivar mixtures. These findings improved insights into how beneficial microbial communities in the rhizosphere contributed to the positive effects observed in cultivar mixtures.